Effect of Emerging Micropollutants on the Anaerobic Digestion of Sewage Sludge - Magdalena Zielińska; Agnieszka Cydzik-Kwiatkowska (Energies, 2024)
The recovery of valuable resources from wastewater treatment plants (WWTPs) has received a great deal of attention as part of the concept of a circular economy. Anaerobic digestion for stabilizing sewage sludge in WWTPs, which produces biogas and stabilized biosolids, is a mature technology used worldwide. However, despite the necessity of achieving safe and reliable organic recycling, studies on the effect of some emerging micropollutants on this process are rare. This knowledge gap is of growing relevance because of the increasing use of some endocrine-disrupting compounds (EDCs), microplastics (MPs), and engineered nanoparticles (NPs) in industry and human life. These compounds are ubiquitous in wastewater streams and, therefore, may have serious effects on the course of the anaerobic digestion of sewage sludge, raising concerns about their effects on the environment. This article provides a comprehensive overview of the mechanisms by which selected EDCs, MPs, and NPs affect the valorization of sewage sludge, with a focus on the production of CH4, H2, and volatile fatty acids. This study takes into consideration the performance during all stages of anaerobic digestion, the shifts in microbial abundance and diversity, and the activity of key enzymes during the treatment process.